Technical Note: A planning technique to lower normal tissue toxicity in lung SBRT plans based on two likely dependent RTOG metrics. Issue 5 (24th March 2018) - Narayanasamy, Ganesh; Desai, Dharmin; Morrill, Steven; Zhang, Xin; Galhardo, Edvaldo; Maraboyina, Sanjay; Penagaricano, Jose
Abstract : Purpose: Intermediate‐ and low‐dose falloff in stereotactic body radiotherapy (SBRT) of lung tumor is known to relate to normal tissue toxicity. The purpose is twofold to analyze the relation between RTOG parameters (namely, R50%, D2cm) in lung SBRT plans and to explore planning methods that correlate with higher than acceptable dose to normal tissue. Methods: RTOG recommended target dose coverage, conformity index, homogeneity index, R50%, and D2cm were evaluated retrospectively in 105 lung tumor SBRT plans. Deviations in R50% and D2cm were correlated with parameters including prescription dose, tumor location, number of beams or arcs, beam configuration (coplanar or noncoplanar), type of treatment plan (3D‐CRT, IMRT or volumetric arc therapy), and shortest distance to the chest wall. Result: All plans met the target coverage, conformity index, homogeneity index, and critical organ dose tolerance objectives. Dose falloff product (DFP) of R50% and D2cm has a small variance and small dependence on PTV. Low correlation between DFP and PTV suggests that R50% and D2cm are not independent. Coplanar beam placement was found to be prevalent among plans with large deviations in R50%, D2cm. Conclusion: This study questions the independence of the two RTOG recommended metrics, R50% and D2cm in lung SBRT plans, and suggests that noncoplanar beams may provide better normal tissue sparing by reducing the intermediate dose falloff.